Risk factors for hospitalizations associated with depression among women during the years around a birth: a retrospective cohort study - Fairthorne, Jennifer Christine; Oberlander, Tim F; Brant, Rollin; Hanley, Gillian E (International Journal of Population Data Science, 2021)
Introduction Socio-economic status (SES) is an important determinant of health and low SES is associated with higher rates of prenatal and post-partum depression while prenatal and post-partum depression are associated with sub-optimal maternal and infant health. Furthermore, increased negative effects of post-partum depression have been reported in children from low SES backgrounds. Objectives To assess whether socio-economic status (SES) was related to the risk of a medical or psychiatric hospitalization associated with depression (HAWD) and the risk of a HAWD by anti-depressant (AD) use during the years around a birth Methods This retrospective cohort study used linked birth, hospitalization, prescription and tax-file records of the study cohort. We linked registry data of 243,933 women delivering 348,273 live infants in British Columbia (1999-2009). The outcomes of interest were a HAWD and a HAWD and the associated patient anti-depressant (AD) use. Ranked area-based measures of equivalised, family disposable income were used to create income deciles (Decile-1 low), our proxy for SES. Mothers from Decile-6 were the comparator group. Anti-depressant use was defined as having a prenatal prescription for a serotonin reuptake inhibitor or other AD and the years around a birth were the period beginning 12 months before conception and ending 12 months after the birth. We analysed by pregnancy using mixed effects logistic regression whilst adjusting for maternal age and parity. Results Compared to middle-income mothers from Decile-6, (Decile-1, Decile-2) mothers from low income neighbourhoods had increased odds of HAWDs [aOR=1.77(CI: 1.43, 2.19); aOR=1.56(CI: 1.26, 1.94)]. Mothers from low income areas with depression and no AD use had even higher odds of HAWDs [aOR=1.83(CI: 1.33, 2.20); aOR=1.71(CI: 1.33, 2.20)]. Conclusions Results provide preliminary evidence that barriers to treating depression with ADs in mothers from low income areas during the years around a birth might contribute to their increased risk of a hospitalization associated with non-pharmacologically treated depression. Further research is implicated to further elucidate the origins of this increased risk. Keywords Mothers; Socio-economic status; Antidepressive agents; Pregnancy; Post-partum period; Parturition; Prescriptions; Hospitalization. Disclaimer All inferences, opinions, and conclusions drawn in this manuscript are those of the authors and do not reflect the opinions or policies of the Data Stewards of Population Data BC.